2020
DOI: 10.1186/s12978-020-00967-y
|View full text |Cite
|
Sign up to set email alerts
|

Barriers of access and utilization of reproductive health services by adolescents-Khartoum state-Sudan-2020: study protocol

Abstract: Background: Adolescence is widely defined as the time in life when the developing individual attains the skills and attributes necessary to become a productive and reproductive adult. Most adolescents are healthy, but there is still substantial premature death, illness, and injury among adolescents. Illnesses can hinder their ability to grow and develop to their full potential. Alcohol or tobacco use, lack of physical activity, unprotected sex and/or exposure to violence can jeopardize not only their current h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Another possible reason could be a lack of confidence and fear of being seen by friends or family, preferences, sexual activity status, childbearing status, the difference in socioeconomic condition, and lack of comprehensive knowledge and unfavorable attitudes. 19,20 The results of this study revealed that disabled youths aged 20-24 years were 2.9 times more likely to use YFRHS than individuals between the ages of 15 and 19 years. Consistently, a study conducted in the Gondar zone revealed that the utilization of SRH is more among the age of 18 years and above as compared with ages <15 years.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Another possible reason could be a lack of confidence and fear of being seen by friends or family, preferences, sexual activity status, childbearing status, the difference in socioeconomic condition, and lack of comprehensive knowledge and unfavorable attitudes. 19,20 The results of this study revealed that disabled youths aged 20-24 years were 2.9 times more likely to use YFRHS than individuals between the ages of 15 and 19 years. Consistently, a study conducted in the Gondar zone revealed that the utilization of SRH is more among the age of 18 years and above as compared with ages <15 years.…”
Section: Discussionmentioning
confidence: 71%
“…Probable justification could be poor access to reproductive health choices from facility level barrier, social barrier, or provider level barrier. Another possible reason could be a lack of confidence and fear of being seen by friends or family, preferences, sexual activity status, childbearing status, the difference in socioeconomic condition, and lack of comprehensive knowledge and unfavorable attitudes 19,20 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 35 Overall, these findings should draw the attention of health policymakers in Sudan to pay more attention to women’s health needs and reduce access barriers to reproductive health services in Sudan, which were regarded as a pressing health challenge in the region. 36 …”
Section: Discussionmentioning
confidence: 99%